PENGARUH LEVERAGE, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PT JAKARTA SETIABUDI INTERNASIONAL, TBK. YANG TERDAFTAR DI BURSA EFEK INDONESIA - Virya Shanti; Liper Siregar; Ady Inrawan; Sepbeariska Manurung (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The purpose of this research are to find out the description of leverage, profitability, dividend policy and company value and to determine the effect of leverage, profitability, and dividend policy on the value of the company both simultaneously and partially at PT Jakarta Setiabudi Internasional, Tbk. registered on the Indonesian Stock Exchange. This research was conducted using qualitative descriptive analysis methods and quantitative descriptive analysis. The method used to analyze the data in this study is the classical assumption test, multiple linier regression analysis, the correlation coefficient, coefficient of determination, and hypothesis test (F test and t test). Testing is performed using the SPSS Version 20 software program.The results of the research can be summarized of follows: 1) Leverage and profitability fluctuate and tend to decline while dividend policies and corporate values fluctuate and tend to increase 2) Regression results indicate that there is a positive influence between leverage, profitability, dividend policy on the value company at PT Jakarta Setiabudi Internasional, Tbk. registered on the Indonesian Stock Exchange.Suggestions from this research are companies should make efficient use of costs and use equity effectively to increase sales so that profits increase and profitability will also increase. Companies should also pay attention to debt management, profitability and company dividend policies. Keywords: Leverage, Profitability, Dividend Policy, and Company Value